Multicolumn spinal cord stimulation for predominant back pain in failed back surgery syndrome patients: a multicenter randomized controlled trial. Issue 6 (June 2019) - Rigoard, Philippe; Basu, Surajit; Desai, Mehul; Taylor, Rod; Annemans, Lieven; Tan, Ye; Johnson, Mary Jo; Van den Abeele, Carine; North, Richard
Abstract : Abstract: Despite optimal medical management (OMM), low back pain (LBP) can be disabling, particularly after spinal surgery. Spinal cord stimulation (SCS) is effective in reducing neuropathic leg pain; however, evidence is limited for LBP. This prospective, open-label, parallel-group trial randomized (1:1) failed back surgery syndrome (FBSS) patients with predominant LBP to SCS plus OMM (SCS group) or OMM alone (OMM group) at 28 sites in Europe and the Americas. If trial stimulation was successful, a multicolumn SCS system was implanted. Outcomes were assessed at baseline (before randomization) and at 1, 3, 6, and 12 months after randomization. Patients could change treatment groups at 6 months. The primary outcome was the proportion of patients with ≥50% reduction in LBP (responder) at 6 months. Secondary outcomes included change in pain intensity, functional disability, and health-related quality of life (HRQoL). The results are posted at ClinicalTrials.gov under registration number NCT01697358. In the intent-to-treat analysis, there were more responders in the SCS group than in the OMM group (13.6%, 15/110 vs 4.6%, 5/108, difference 9% with 95% confidence interval 0.6%-17.5%, P = 0.036) at 6 months. The SCS group improved in all secondary outcomes compared with the OMM group. The OMM group only improved in HRQoL. In the SCS group, 17.6% (18/102) experienced SCS-related adverse events through 6 months, with 11.8% (12/102) requiring surgical reintervention. Adding multicolumn SCS to OMM improved pain relief, HRQoL, and function in a traditionally difficult-to-treat population of failed back surgery syndrome patients with predominant LBP. Improvements were sustained at 12 and 24 months. Abstract : Supplemental Digital Content is Available in the Text.Adding multicolumn spinal cord stimulation to optimal medical management improved pain relief, health-related quality of life, and function in a traditionally difficult to treat population of failed back surgery syndrome patients with predominant low back pain.